Facile, fast, and inexpensive synthesis of monodisperse amorphous Nickel-Phosphide nanoparticles of predefined size - Mandel, Karl; Dillon, Frank; Koos, Antal A.; Aslam, Zabeada; Jurkschat, Kerstin; Cullen, Frank; Crossley, Alison; Bishop, Hugh; Moh, Karsten; Cavelius, Christian; Arzt, Eduard; Grobert, Nicole (Chemical Communications, 2011)
Monodisperse, size-controlled Ni-P nanoparticles were synthesised in a single step process using triphenyl-phosphane (TPP), oleylamine (OA), and Ni(ii)acetyl-acetonate. The nanoparticles were amorphous, contained ∼30 at% P and their size was controlled between 7-21 nm simply by varying the amount of TPP. They are catalytically active for tailored carbon nanotube growth. © 2011 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2020-04-02